2020
DOI: 10.1038/s41598-020-72780-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of hyperuricemia among urban adults aged 35–79 years in southwestern China: a community-based cross-sectional study

Abstract: Hyperuricemia is prevalent throughout the world. However, a well-designed large-scale epidemiological investigation of hyperuricemia in southwestern China is lacking. A regional representative sample of 10,141 participants were included using multistage, stratified sampling in Chengdu and Chongqing from September 2013 to March 2014. Hyperuricemia was defined as the self-reported of the doctor's diagnosis of hyperuricemia, or serum uric acid > 420 μmol/L in men or serum uric acid > 360 μmol/L in women. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 44 publications
1
18
2
Order By: Relevance
“…The risk of sudden death in obese patients is quite high, even in the absence of organic heart disease, which may be associated with metabolic syndrome. 13 It has been shown by various prospective studies that HUA is an independent risk factor of obesity. 2 Compared with subjects with normal weight, obese subjects have significantly higher levels of SUA and components of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of sudden death in obese patients is quite high, even in the absence of organic heart disease, which may be associated with metabolic syndrome. 13 It has been shown by various prospective studies that HUA is an independent risk factor of obesity. 2 Compared with subjects with normal weight, obese subjects have significantly higher levels of SUA and components of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“… 39 The difference may be explained by the different lifestyles and economic level in the two different areas, which are also closely related to hyperuricaemia. 40 Our determined prevalence was also slightly higher than that in southwest (Chengdu and Chongqing) China hyperuricaemia survey, which showed that the prevalence of hyperuricaemia was 13.5% in 2013–2014 10 . This indicates that we should pay more attention to hyperuricaemia due to the prevalence is increasing with the improvement of economic level and lifestyles changes.…”
Section: Discussionmentioning
confidence: 57%
“…Meanwhile, various major risk factors for hyperuricaemia have been found, such as low economic status,9 obesity10and smoking,11 and some studies have found a link between sleep-disordered breathing and hyperuricaemia 12–17. However, the association of snoring and hyperuricaemia has been studied much less extensively.…”
Section: Introductionmentioning
confidence: 99%
“…While a cross-sectional study in Thailand showed the prevalence of HUA was 10.6% (18.4% in men and 7.8% in women) [10], which is higher than in the US, obviously. A community-based cross-sectional study showed the prevalence of HUA among adults aged 35-79 years was 13.5% (17.3% in men and 10.0%in women) in southwestern China [11]. Meta-analysis indicated that the pooled prevalence of HUA was 17.4% (ranged from 15.5 to 24.6% by regions) among the general population in mainland China, which had become another common metabolic disease after diabetes [12].…”
Section: Discussionmentioning
confidence: 99%